A Multicenter Randomized Trial to Determine the Effect of an Environmental Disinfection Intervention on the Incidence of Healthcare-Associated Clostridium difficile Infection. (2nd May 2017) - Ray, Amy J.; Deshpande, Abhishek; Fertelli, Dennis; Sitzlar, Brett M.; Thota, Priyaleela; Sankar C, Thriveen; Jencson, Annette L.; Cadnum, Jennifer L.; Salata, Robert A.; Watkins, Richard R.; Sethi, Ajay K.; Carling, Philip C.; et al.
Abstract : OBJECTIVE: To determine the impact of an environmental disinfection intervention on the incidence of healthcare-associated Clostridium difficile infection (CDI). DESIGN: A multicenter randomized trial. SETTING: In total, 16 acute-care hospitals in northeastern Ohio participated in the study. INTERVENTION: We conducted a 12-month randomized trial to compare standard cleaning to enhanced cleaning that included monitoring of environmental services (EVS) personnel performance with feedback to EVS and infection control staff. We assessed the thoroughness of cleaning based on fluorescent marker removal from high-touch surfaces and the effectiveness of disinfection based on environmental cultures for C. difficile . A linear mixed model was used to compare CDI rates in the intervention and postintervention periods for control and intervention hospitals. The primary outcome was the incidence of healthcare-associated CDI. RESULTS: Overall, 7 intervention hospitals and 8 control hospitals completed the study. The intervention resulted in significantly increased fluorescent marker removal in CDI and non-CDI rooms and decreased recovery of C. difficile from high-touch surfaces in CDI rooms. However, no reduction was observed in the incidence of healthcare-associated CDI in the intervention hospitals during the intervention and postintervention periods. Moreover, there was no correlation between the percentage of positive cultures after cleaning of CDI or non-CDI rooms and the incidence of healthcare-associated CDI. CONCLUSIONS: An environmental disinfection intervention improved the thoroughness and effectiveness of cleaning but did not reduce the incidence of healthcare-associated CDI. Thus, interventions that focus only on improving cleaning may not be sufficient to control healthcare-associated CDI. Infect Control Hosp Epidemiol 2017;38:777–783